Designing the obvious : a common sense approach to web and mobile application design. - Hoekman, Robert, ....- (Berkeley : New Riders, 2011)
Designing the Obviousbelongs in the toolbox of every person charged with the design and development of Web-based software, from the CEO to the programming team. Designing the Obvious explores the character traits of great Web applications and uses them as guiding principles of application design so the end result of every project instills customer satisfaction and loyalty. These principles include building only whats necessary, getting users up to speed quickly, preventing and handling errors, and designing for the activity.Designing the Obviousdoes not offer a one-size-fits-all development process--in fact, it lets you use whatever process you like. Instead, it offers practical advice about how to achieve the qualities of great Web-based applications and consistently and successfully reproduce them.